Pengujian Black Box pada Sistem Pembayaran SPP di Universitas Unggul dengan Metode Equivalence Partitions - Evi Prasetyani; Eggy Ryan Agvi Riansyah; Habibullah Habibullah; Waisul Kurni; Aries Saifudin (CV. Multi Kreasi Media, 2022)
The introduction of campus management has been assisted by the implementation of an integrated tuition fee system at the University of Excellence. The SPP online payment system is more accessible to users. Software features for SPP payment systems that are integrated with appropriate component procedures must be tested to justify the desired operation and improve system performance so that it can be used according to user preferences. In order to distribute test cases that are considered suitable for testing the integrated SPP payment system, this procedure links the test by segmenting the program input zone into types of information. Totally integrated SPP payment system runs successfully, for the results of the test. But other functions do not exist, and some system output does not change. It is hoped that the system can be used according to user needs based on the findings of this test. 53 of the 61 items tested were suitable, on the other hand 8 were not suitable or less successful than expected. In order to correct deficiencies in the integrated SPP payment system, test findings must be considered.